Sort by

- Relevance
- |Time

... the RHS now becomes 1 - cos^2A Now we have

**LHS**and RHS as sin^2 A = 1 - cos^2A Adding cos^2A...1 Answers · Education & Reference · 12/02/2014

...5x - 2 = 2m for m ∈ Z So 5x = 2m + 2 This implies

**LHS**is even. So x is even too, i.e. x = 2n for n ∈ Z...1 Answers · Education & Reference · 10/02/2014

...2 variables x and y. And the function is y = f(x), where

**LHS**is some function of x. Therefore all you have is one variable...1 Answers · Education & Reference · 07/02/2014

...1) take exponential of both sides. Doing that gets rid of ln on

**LHS**- 3x + 3 = exp (2) 2) subtract 3 from both sides 3x = exp(2) - 3 3) ...2 Answers · Education & Reference · 06/02/2014

...of the radical by squaring both sides x^2 = 5000 - 2p^3 then on

**LHS**d(x^2) /dx = 2x On RHS d(5000)/dx = 0 d (-2p^3) dx = -6p^2...1 Answers · Education & Reference · 06/02/2014

...y I also cannot tell if 2 is a coefficient or exponent on

**LHS**. And neither can I tell what the numerator is on**LHS**in...1 Answers · Education & Reference · 04/02/2014

... these 2 identities and some algebraic manipulations, the

**LHS**can be rewritten as 2cos(x)^2 + sin(x)^2 - 1 and f (x) = sqrt [ 2cos...1 Answers · Education & Reference · 30/01/2014

**LHS**: 4^(x-1)=(2^2)^(x-1)=2^(2x-2) RHS: 32^4=(2^5)^4=2^20 Therefore 20=2x-2 x=111 Answers · Education & Reference · 24/01/2014

... -- We cross multiply both

**LHS**and RHS (cos (2x)) ( 1 - tan (x)) = (1+ tan(x)) (1 - sin(2x)) Expanding...1 Answers · Education & Reference · 28/01/2014

... that we are done with the RHS, we have to work on the

**LHS**cos(2A) = cos (A+A) = cos A cos A - sin A...1 Answers · Education & Reference · 26/01/2014